Review of modifications to indirect land use change modeling and resulting carbon intensity values within the California Low Carbon Fuel Standard regulations - Leland, Amber; Hoekman, S. Kent; Liu, Xiaowei (Vivian) (Journal of cleaner production, 2018)
The California Low Carbon Fuel Standard (LCFS) regulations were recently re-adopted (2015) with numerous revisions to the 2009 LCFS. Many aspects of the California Air Resources Board's (CARB) approach to modeling indirect land use change (ILUC) emissions have changed, including significant updates to the Global Trade Analysis Project (GTAP) agro-economic model and use of a new emission factor (EF) database derived from the Agro-Economic Zone Emission Factor (AEZ-EF) model. These revisions have resulted in significantly reduced Carbon Intensity (CI) values for many biofuel pathways, making them more attractive to meet greenhouse gas (GHG) reduction targets. The objective of this work was to investigate the most significant changes made to CARB's approach of modeling ILUC, the reasons for these changes, and their impacts on calculated CI values of biofuels. In this effort, land use change (LUC) estimates from GTAP and the AEZ-EF emission factors (EF) were compared to previous values. A new subset of land type, referred to as "cropland-pasture" has been incorporated into the GTAP-BIO model, and now constitutes the bulk of LUC for corn ethanol, soy biodiesel and sugarcane ethanol. However, since EFs of cropland-pasture are not well established, the AEZ-EF model simply applies an EF that is equivalent to 50% of the EF for conversion of pasture to cropland for the same AEZ region. In addition, differences in carbon accounting between perennial crops and annual crops contribute significantly to large reductions in sugarcane CI. These influential assumptions require further investigation. •Significant changes to ILUC modeling have been adopted in the 2015 LCFS.•Cropland-pasture (CP) in the U.S. and Brazil makes up the bulk of LUC.•The EFs for CP are not well defined, and taken as a fraction of other land types.•Soil emissions are ignored for perennial crops in the AEZ-EF model.